2019 Kansas Performance Tests with Winter Wheat Varieties - Lingenfelser, Jane (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2018)
The 2019 winter wheat growing season in Kansas was a tale of two crops: one extremely challenged (though resilient) crop in the central and eastern portions of the state, and a crop that was exposed to near-optimal conditions in western Kansas.
SRP1151
Keywords: Wheat; Crop development; Diseases; Weather; Kansas; SRP1151